(untitled) (Nordic Journal of African Studies, 2020)
Book Review ESTERHUYSEN Pieter (ed.), 1998. AFRICA A-Z: CONTINENTAL AND COUNTRY PROFILES. Pretoria: Africa Institute of South Africa. 373 pp. (A-4 size), + 20 pp. references and index. ISBN 0-7983-0135